Automated Brain Tumor Detection and Classification - Kumar.T, Sathis; Amirtha.V; Srimathi.E; Yuvasri.B (Journal of Soft Computing Paradigm, 2024)
Accurate and timely diagnosis of brain tumors is vital for improving patient outcomes and guiding treatment. Traditional diagnostic methods can be subjective and inconsistent, making automated systems that use deep learning and machine learning technologies essential. This research develops a Python-based system using Matplotlib, Pandas, NumPy, TensorFlow, Keras, and OpenCV for brain tumor classification. OpenCV handles MRI image preprocessing tasks such as segmentation and normalization, which are crucial for accurate analysis. Convolutional Neural Networks (CNNs) implemented with TensorFlow and Keras offer precise tumor classification. NumPy supports data handling, pandas manages dataset organization, and Matplotlib produces visual representations of the results. The Brain Tumor Segmentation (BraTS 2021) dataset is used for training and testing. The performance is measured using accuracy, precision, recall, and F1-score. The CNN models like ResNet 50, Inception-V3, EfficientNetB3 and VGG16 is compared in the study to conclude with the optimal method to improve classification robustness. This study would enhances diagnostic tools in medical imaging by identifying an optimal algorithm for precision medicine, aiming for early diagnosis, improved treatment outcomes, reduced workload for healthcare professionals, and better public health.